Benefits of Wayang Kamasan Klungkung Bali in Improving Dignified Cultural Character and Sustainability of International Tourism - Ni Ketut Wiriani Merta; I Putu Sudana; Yohanes Kristianto (Jurnal Multidisiplin Madani, 2023)
So great is the importance of the meaning of Kamasan paintings as previous writers have explored the uniqueness and attractiveness of kamasan klungkung paintings. Wayang art is very full of meanings as in the study of writing: The Role of Painting as a Critical Media in the Industrial Revolution Era (Gusti Agung Widia Widyasari), namely painting is not a display item but as an intermediary for imformation and criticism, then the study unravels the meaning of Kamasan puppet painting in Puri Klungkung (Tzabit Azimer Ahmad) which peels Kamasan paintings telling books such as Adiparwa, Tantri, Sutasoma, and the lives of the Gods.Then the teachings of Hinduism as inspiration for the creation of traditional Balinese painting works (Wayan Agus Gunada). Painting is part of the art of Kamasan puppet art has unique cash characteristics such as natural forms, folklore, mythology and Hindhu religious teachings, which are manifested in the forms of symbols in it that are thick with spiritual value. Painting is not only as a display material but also as a material for forming human characters. Because in puppets there are good teachings and bad teachings. In puppets there are ways of behaving, ways of thinking, ways of dealing with life are all contained in puppet stories. Positive characters bring peace while negative characters bring misery. For example, Ravana, a puppet character who has a great lust that cannot hold back his ego, then makes all people miserable, Korawa who loba makes the entire palace miserable. Likewise, the wise character of Rama, the wise admiral character can be used as an example in behaving in everyday life. The reason for this research is to preserve traditional art assets as one of the wealth of the Indonesian nation (Bali). To introduce Indonesia in international especially tourism. While the uniqueness of painting is: 1 as the meaning of life / philosophical learning. 2 Wayang paintings have survived until now not extinct 3, puppet paintings as an economic breakthrough of the community, 4 Puppet paintings of ancestral assets, 5 Wayang paintings as friends of tourism to come to Indonesia.Almost all corners in the Sangging Kamasan Klungkung Bali banjar, there are puppet painting galleries that are ready to welcome tourisms visiting Indonesia, especially Bali. Great services of classical puppet painting or Balinese Traditional Paintings as a loyal friend of tourism, so that Indonesia can get acquainted with international countries because of the contribution of this classic puppet painting service (Balinese Traditional Paintings)